Youth empowerment in agriculture through participation in youth integrated training farm project in Kwara State, Nigeria - Ayinde, Latopa Abdul Lateef (2016)
Youth empowerment in agriculture has become a strategy to address the high rate of youth unemployment in Nigeria which The United Nations Development Program report shows is one of the worst in Africa sub-Sahara at 37.7%. The much sought after white collar jobs and over dependent on oil business that generates quick returns on investment are no longer available.As a result, the Government has embarked on youth empowerment in agriculture programs at the National, State, and Local Government levels to tackle the overbearing unemployment rate to reduce crime, and youth restiveness. However, years after some states in Nigeria embarked on youth empowerment projects in agriculture, there are indications that the rate of youth participation in the youth empowerment in agriculture programs is declining.The decline was attributed to the interplay between the youth empowerment in agriculture programs and the process of participation which has contributed to the persistent unemployment rate.With this background, this study was designed to explore and understand through obtaining qualitative information from informants on how youth empowerment in agriculture is achieved through youth participation in the Youth Integrated Training Farm (YITF) project in Kwara State Nigeria. Qualitative case study approach was adopted for the study with multiple methods of data collection which includes interviews, observation, documents, and focus group discussions (FGD).Findings revealed that the process of youth participation in the youth empowerment in agriculture project in YITF involves nine stages which lead to youth empowerment in agriculture in economic, social and psychological dimensions.However, the 9th stage which is empowerment incentives (startup capital) was not fully met and therefore, contributed to the decline in youth participation. Findings also show that, apart from the implementers and the Zimbabwean farmers, the roles and contributions of the stakeholders in the youth empowerment in agriculture in YITF were not impressive. The study revealed that the factors that are responsible for the decline in youth participation in the youth empowerment in agriculture include the youth mindset, government induced, environmental and other youth empowerment projects in Kwara State. However, it was found that the youth empowerment in agriculture project has impacts the youth directly by rekindling their interest in agriculture business, improves their capacity to create wealth, and change their attitudes from disoriented to oriented. Indirectly, the youth empowerment in agriculture project has contributed to a reduction in youth unemployment, youth truancy and crime rate in the state.The study concludes that youth are empowered in agriculture individually and as groups in terms of capacity building through their participation in the YITF project but not fully empowered in terms of meeting the project objectives. This was as a result of the government inability to meet the 9th step of the process of participation which affects the rate of youth participation and vision of the project to groom a new generation of commercial farmers. However, the project contributes to youth selfefficacy in agriculture in Kwara State through job creation and job opportunities in agriculture business. The youth empowerment in griculture in YITF project faces some barriers in the participation process which resulted in discouragement in the project,lack of trust in government and subsequently, the decline in the youth participation. Recommendations were gathered from the informants as key players on how to tackle these barriers so that achieving youth empowerment in agriculture through youth participation will be enhanced.